ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM FILM SANG PENCERAH ARAHAN HANUNG BRAMANTYO - Khairunnisa Khairunnisa; Marsiah Marsiah; Sulistyowati Sulistyowati (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: This study aims to describe the story in the film Sang Pencerah and to describe the values of its Islamic education. This research uses a descriptive qualitative approach. The subject of this research is the film Sang Pencerah and its object is the values of Islamic education. The data in this study were collected through observation, documentation, and literature study. Data analysis using analysis from the theory of Roland Barthes. The results showed that: 1) The story contained in the film Sang Pencerah is K.H. Ahmad Dahlan's struggle in rectifying Islam and opening new, more modern insights so that someone's misunderstanding in knowing Islam does not occur. 2) Found in the film Sang Pencerah, there are values of Islamic education, namely; a) the values of the faith in the form of; prohibition of committing shirk / associating partners with Allah SWT and submitting to Allah, b) The values of worship inOL the form of; establishing prayers on time, recitation, performing the Hajj and getting married, c) moral values in the form of; please help, give alms, be patient, respect each other, and be polite in words and deeds. Keywords: Islamic education, values, Islamic film